2022
DOI: 10.3390/ani12192491
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Anxiety and Stress among Youth in a CBT-Based Equine-Assisted Adaptive Riding Program

Abstract: Reining in Anxiety (RiA) is a therapeutic program for youth with mild to moderate anxiety delivered in a therapeutic riding setting by Certified Therapeutic Riding Instructors. RiA was developed after a review of the evidence base for youth anxiety, is manualized, and includes five core CBT components: in vivo exposure, cognitive restructuring, youth psychoeducation, relaxation, and caregiver psychoeducation about anxiety. This study extended findings from a prior RCT that examined (1) the feasibility of colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…are important to measure in A/TR practice. The outcome constructs identified by respondents are consistent with research findings in the A/TR literature; specifically, research has demonstrated that A/TR can improve mental functions ( 33 ), social functioning ( 34 ), emotional regulation skills ( 35 ), communication skills ( 34 ), physical function ( 36 , 37 ), quality of life ( 38 , 39 ), and community integration ( 40 ). Given these findings, a battery of standardized outcome assessments proposed for use in the A/TR setting should measure a wide variety of outcomes in A/TR participants from a variety of age groups, diagnoses, and life experiences.…”
Section: Discussionsupporting
confidence: 75%
“…are important to measure in A/TR practice. The outcome constructs identified by respondents are consistent with research findings in the A/TR literature; specifically, research has demonstrated that A/TR can improve mental functions ( 33 ), social functioning ( 34 ), emotional regulation skills ( 35 ), communication skills ( 34 ), physical function ( 36 , 37 ), quality of life ( 38 , 39 ), and community integration ( 40 ). Given these findings, a battery of standardized outcome assessments proposed for use in the A/TR setting should measure a wide variety of outcomes in A/TR participants from a variety of age groups, diagnoses, and life experiences.…”
Section: Discussionsupporting
confidence: 75%
“…Simultaneously, affiliative bonding may also be occurring, which may impact negative stress. The same non-significant trends were echoed in both the horses and riders' experiences [12][13][14] giving additional evidence of the interconnectedness of horse, rider, and volunteer.…”
Section: Discussionmentioning
confidence: 68%
“…This study extends the current evidence base by triangulating self-reports with an analysis of saliva to measure cortisol and alpha-amylase (stress indicators), and oxytocin (affiliative bonding, defined as "valuing and enjoying interpersonal closeness with others" [13]). Given the current gaps in knowledge and the limitations of current research, this study was undertaken in order to contribute knowledge about the physiological effects and perceived benefits of volunteering to a research study that tested Reining in Anxiety (RiA), a 10-week manualized intervention that combines adaptive riding and core concepts of cognitive behavioral therapy [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Shearer et al (2016) implemented a four-week intervention involving mindfulness practices and interaction with dogs, noting significant reductions in anxiety levels through both approaches. Hoagwood et al (2022) incorporated Cognitive Behavioral Therapy (CBT) principles and found that equine-assisted adaptive riding programs had a significant impact on reducing anxiety in adolescents.…”
Section: Studies On Companion Animals Improving Human Psychological H...mentioning
confidence: 99%